Persistence versus extinction for two competing species under a climate change - Zhang, Zewei; Wang, Wendi; Yang, Jiangtao (Nonlinear Analysis: Modelling and Control, 2017)
This paper considers effects of a climate-induced range shift on outcomes of two competitive species, which is modeled by a reaction–diffusion system with the increasing growth rates of species along a shifting habitat gradient. Analytical conditions are established for the coexistence or competitive exclusion of two-competitors under the climate change, which present the control strategies to maintain the persistence of species.